Entre três corpos - histórico, biológico, erógeno -: um estudo psicanalítico sobre a obesidade - Rosa, Rodrigo Távora César Fröhlich (2011)
Obesity is one of the conditions that affect human health in an especially intense way in the XXI century. Despite being recognized as a pathology by the World Health Organization it fits in a different profile about what is a disease, due the fact of being named as a Non-transmissible Chronic Disease, a concept that demands a rethink about what would be health and illness towards a condition that deteriorates the human being, both physically and mentally, although in a slow manner and not an acute one. The rate in which obesity has reached epidemic proportions in several countries also leads to a deep consideration about the historical and cultural aspects that brought it to the current prevalence in several places of the planet nowadays. By becoming the object of study of several fields of the human knowledge, obesity ends up producing a permanent focus of tension between the several branches of science that study it, since each of them highlight one or another factor of the many that compose it. The proposal of this research that is presented throughout the text seeks to unite relevant information regarding obesity that belong to many areas of the scientific knowledge, gathering them in a way to produce a questioning about the status of obesity towards Psychoanalysis. When questioning the possibility of obesity to become an object of study of the psychoanalytical research the need for metapsychological foundation arises that would allow representing it both within the theory and practice in Psychoanalysis. The search for concepts that could explain the psychological suffering of the obese brought to the text a study about the founding of the feeding function, as of the feeling of satiety and other early body sensations, and the possibility that a perversion in the usage of such sensations may be used in the way that obese use them to handle the daily challenges that are brought upon their psyche. The obese body also carries a questioning about the notion of body in Psychoanalysis that could be useful in its understanding, as in which treatment methods would prove to be useful in such specific cases. The contribution of Hilde Bruch, psychoanalyst, is presented as one of the keystones upon which this text could be written, specially by suggesting the existence of two types of obesity, reactive and development, and also a specific therapeutic approach to both cases. Through the description of two clinical cases the obesity types and their treatment are portrayed, which aims to corroborate the metapsychological description that uses the actual neurosis model as a suggested concept to explain the psychological suffering of the obese, marked by an anxiety that lacks symbols to express itself. The ultimate proposal of this text is that obesity may be an important point of convergence for the dialogue between many scientific fields, including Psychoanalysis, that can produce rich contributions in future studies, especially if an interdisciplinary dialogue is pursued